Compound Homozygous Rare Mutations in PLCE1 and HPS1 Genes Associated with Autosomal Recessive Retinitis Pigmentosa in Pakistani Families - Masroor Ellahi Babar; Akhtar Ali; Syed Hassan Abbas; Mirza Jawad ul Hasnain; Nida Babar; Hira Babar; Tanveer Hussain; Asif Nadeem; Namra Ayub; Sundus Shahid; Muhammad Tariq Pervez (Tehran University of Medical Sciences, 2022)
Background: Retinitis pigmentosa (RP) belongs to pigmentary retinopathies, a generic name for all retinal dystrophies with a major phenotypical and genotypical variation, characterized by progressive reduction of photoreceptor functionality of the rod and cone. Global prevalence of RP is ~ 1/4000 and it can be inherited as autosomal dominant (adRP), autosomal recessive (arRP) or X- linked (xlRP). We designed this study to identify causative mutations in Pakistani families affected with arRP. Methods: In 2019, we recruited two unrelated Pakistani consanguineous families affected with progressive vision loss and night blindness from Punjab region. Clinical diagnosis confirmed the; bone spicule pigmentation of the retina, and an altered electroretinogram (EGR) response. Proband and healthy individual from each family were subjected for whole-exome sequencing (WES).  Various computational tools were used to analyze the Next Generation Sequencing (NGS) data and to predict the pathogenicity of the identified mutations. Results: WES data analysis highlighted two missense homozygous variants at position c.T1405A (p.S469T) in PLCE1 and c.T11C (p.V4A) in HPS1 genes in proband of both families. Healthy individuals of two families were tested negative for p.S469T and p.V4A mutations. The variant analysis study including molecular dynamic simulations predicted mutations as disease causing.  Conclusion: Compound effect of mutations in rarely linked PLCE1 and HPS1 genes could also cause RP. This study highlights the potential application of WES for a rapid and precise molecular diagnosis for heterogeneous genetic diseases such as RP.